Hubungan Antar Kebiasaan Membaca dengan Penguasaan Kosa Kata Bahasa Inggris Siswa - Elizabeth Meiske Maythy Lasut (STKIP Andi Matappa Pangkep, 2022)
Mastery of English vocabulary is one of the academic goals teachers expected students achieve. It becomes a problem if the goal is not attained. From various previous research results, it was found out that there were predictors of this failure, and one of which was students reading habit. This quantitative, descriptive-correlative research tried to analyze and answer the research questions whether students’ English vocabulary has a correlation with their reading habit. The instrument was distributed to 70 sixth grade students who were the respondents of this study. The data were analyzed using the Mean Score and Pearson Correlation. The results obtained showed that the frequency of reading was only occasionally, with sufficient time, and moderate attitude towars reading. In addition, it was found that the level of English vocabulary achievement was only moderate level. Finally, this study also proved that students reading frequency, time spent, and attitude towards reading have significant relationships with the level of students’ English vocabulary achievement. All of these relationships showed a positive direction. Therefore, it is suggested that English teachers should encourage their students to do lot of reading activities, and to give them reading tasks that should be done in the school library.